2013
DOI: 10.1159/000354898
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Laser Dichorionization of the Placenta in the Treatment of Severe Twin-Twin Transfusion Syndrome

Abstract: Objectives: To describe the results of a technique of laser ablation of placental vessels in the treatment of severe twin-twin transfusion syndrome (TTTS), which is characterized by separation of the fetoplacental vascular territories and dichorionization of the placenta. Patients and Methods: Descriptive analysis of TTTS cases treated with the endoscopic laser dichorionization of the placenta (ELDP) procedure. The variables evaluated were the occurrence of reversal of the donor-recipient phenotype, persistenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Unfortunately these investigators did not report placental injection studies. [11][12][13] Importantly, however, even after the Solomon procedure, we still found a clinically important number of residual anastomoses (19% in the overall Solomon group and 12% in Placentas with arterioarterial residual anastomoses, n (%) 6 (43) 4 (17) .09 3 (38) 2 (11) .10…”
Section: Commentmentioning
confidence: 78%
“…Unfortunately these investigators did not report placental injection studies. [11][12][13] Importantly, however, even after the Solomon procedure, we still found a clinically important number of residual anastomoses (19% in the overall Solomon group and 12% in Placentas with arterioarterial residual anastomoses, n (%) 6 (43) 4 (17) .09 3 (38) 2 (11) .10…”
Section: Commentmentioning
confidence: 78%
“…Fetoscopic surgery is the only treatment for TTTS and it may be indicated in selected cases of sIUGR. Despite its clear benefits, fetal surgery has inherent risks that could affect pregnancy outcome and is associated with increased risks of preterm prelabor rupture of membranes (PPROM) and preterm delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Only few studies have examined pregnancy and neonatal outcomes using equatorial laser for the treatment of TTTS [12][13][14][15][16] . A recent randomized controlled trial has shown that this approach, also called 'Solomon' technique, was associated with a similar dual survival and survival of at least one twin compared to the group treated with the selective technique.…”
Section: Introductionmentioning
confidence: 99%